Exploring Mathematical Attitudes among Primary Teachers: A Comparative Study in Selected District, India - Mirgank, Kislay Kishor; Kalhotra, Satish Kumar (PT. Riset Press International, 2024)
This quantitative study will investigate the mathematical attitudes of primary teachers in Gaya District, Bihar, India, with the aim of understanding how demographic factors will influence these attitudes. By utilizing a modified version of Moreira C.M.'s (1992) Attitude towards Mathematics Inventory, the research has assess teachers' understanding, confidence, and pedagogical approaches in teaching mathematics. Data on gender, location, caste background, qualification, and teaching experiences will be collected through a structured questionnaire. A stratified random sampling technique has ensured representation across demographics, with a targeted sample size of at least 200 primary teachers. Statistical analyses, including t-tests and ANOVA, will be employed to examine the hypotheses regarding gender, location, caste background, qualification, and teaching experiences. The findings are expected to provide valuable insights into the factors shaping mathematical attitudes among primary teachers in a diverse educational context like Bihar, India, contributing to the ongoing educational reforms in the region.